2020
DOI: 10.3390/ijerph17165867
|View full text |Cite
|
Sign up to set email alerts
|

Turning Community Elder Care into a Profession: Insights from Trainees, Developers, Employers and Supervisors

Abstract: This study explores the process of turning elder care into a profession, by giving a voice to different professionals who took part in developing and implementing a new Israeli training program for community care workers. The program attempts to offer a response to the shortage of paid long-term carers for older adults by turning community elder care into a profession. Interviews with graduates, trainees who dropped out of the program, developers, employers and supervisors from three regions of the training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In China, there is a vast gap between the supply and demand of caregivers ( 6 ), which may affect residents' preference for LTCI. Our findings indicate that it is of great necessity for the Chinese government to train and support caregivers ( 70 ) to enable them to deliver adequate and high quality LTC services.…”
Section: Discussionmentioning
confidence: 88%
“…In China, there is a vast gap between the supply and demand of caregivers ( 6 ), which may affect residents' preference for LTCI. Our findings indicate that it is of great necessity for the Chinese government to train and support caregivers ( 70 ) to enable them to deliver adequate and high quality LTC services.…”
Section: Discussionmentioning
confidence: 88%
“…Muramatsu et al [ 24 ] found that home-based and community-based care can effectively improve the mental health level of the disabled older adults. Other studies have shown that the establishment of professional community medical and nursing service institutions can take over the care of the disabled older adults when their families can not take care of them, so as to avoid their worries [ 25 , 26 ]. On the other hand, professional community service institutions can ensure the disabled older adults to seek medical treatment at the first time in case of physical discomfort or emergency, and reduce the treatment risk of the disabled older adults [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The collaboration between family caregivers and community professionals' can effectively improve the mental health level of the disabled elderly [22]. Other studies have shown that the establishment of professional community medical and nursing service institutions can take over the care of the disabled elderly when their families can not take care of them, so as to avoid their worries [23,24]. On the other hand, professional community service institutions can ensure the disabled elderly to seek medical treatment at the rst time in case of physical discomfort or emergency, and reduce the treatment risk of the disabled elderly [25].…”
Section: Introductionmentioning
confidence: 99%